Efficacy of topical local anaesthesia to reduce perioperative pain for endovenous laser ablation of varicose veins: a double-blind randomized controlled trial. (August 2016) - Saha, Sunita; Tiwari, Alok; Hunns, Charlotte; Refson, Jonathan; Abidia, Ahmed
Objectives: Tumescent local anaesthesia via multiple injections in the perivenous space leads to intraoperative and postoperative pain during endovenous laser ablation (EVLA). We considered whether the application of topical local anaesthesia reduces pain caused by these injections. Methods: Eligible patients undergoing local anaesthetic EVLA were recruited and randomized to either application of topical local anaesthesia or water-based gel (placebo) to the inner thigh over the marked great saphenous vein. Varicose vein severity was classified using the American venous forum clinical etiological anatomical pathological (CEAP) classification score for chronic venous disorders and the Aberdeen varicose vein questionnaire (AVVQ) score. Visual analogue pain scores attributable to the varicose veins or tumescent injections were recorded before the procedure, immediately postprocedure and prior to discharge. Secondary outcome measures were extra analgesia requirement during or immediately postoperatively. Analysis was performed using the unpaired Student's t test and Wilcoxon signed-rank test. Results: A total of 52 patients underwent the procedure. Eight patients were excluded from analysis due to failure to complete the procedure or incomplete data. In the remaining 44 patients (24 local anaesthesia, 20 placebo), no statistical difference was noted in age, gender distribution or the severity of varicose veins assessed preoperatively by the clinician (CEAP classification score, median = 2 in both groups) and patient (AVVQ, mean placebo = 21.59, local anaesthesia = 17.53, p = 0.264) between the two groups. There was no statistical difference in pain scores between the placebo and topical local anaesthetic group at baseline (23.0 versus 20.44, p = 0.57), immediately postoperatively (23.35 versus . 19.75, p = 0.44) or predischarge (20.9 versus 13.75, p = 0.68). Conclusions: Topical local anaesthesia is of no benefit in EVLA of varicose vein to reduce patient experience of perioperative pain.